2020
DOI: 10.3390/brainsci10090599
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Pain Modulation Effectiveness: An Experimental Study Comparing Test Paradigms and Analyzing Potential Predictors in a Healthy Population

Abstract: Conditioned pain modulation (CPM) is an endogenous pain inhibition phenomenon that can be summarized simply as one type of pain being able to inhibit another, which must be in a remote area in relation to the first pain. We aimed to compare the effectiveness of four CPM test paradigms as well as the association of the CPM effect with potential predictors in 72 healthy volunteers. Pressure pain from an algometer was used as the test stimulus, and pain provoked by cold water or ischemic pressure was used as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…41, and 0.40, respectively). Although no previous studies have analyzed this relationship, some studies have examined the influence of this variable on pain modulation processes and suggested that the degree of affinity to a specific stimulus could interact in these processes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41, and 0.40, respectively). Although no previous studies have analyzed this relationship, some studies have examined the influence of this variable on pain modulation processes and suggested that the degree of affinity to a specific stimulus could interact in these processes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that other studies did not find a strong correlation between CPT and the other variables because these populations are accustomed to cold, and, therefore, they could have a greater tolerance to cold and would be adapted to this stimulus. For this reason, the measurement of the ‘unpleasant variable’ is recommendable because the affinity for the stimulus could explain many of the results (high affinity for the stimulus would imply a greater tolerance to it and vice versa) [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the intraindividual level, neither the early nor the late effects correlated significantly between both testing paradigms. Although it has been recently recommended to enrich studies and perform different CPM protocols with the same subjects [50], only a few studies have compared the magnitude of the CPM-effect between different CS [51][52][53] or different combinations of CS and TS [54,55]. Significantly different CPM magnitudes were evoked in the same individual depending on the nature of the CS, even when the TS-induced and the CS-induced pain intensity were similar [51].…”
Section: Modality Specific Effectsmentioning
confidence: 99%
“…Little is known however about potential differences in the magnitude of the CPM effect between a sequential or parallel design. Indirect studies reported conflicting results, showing no differences between both designs ( Ibancos-Losada et al, 2020 ), larger effects for either a parallel ( Nahman-Averbuch et al, 2013 ; Ram et al, 2008 ) or sequential ( Enax-Krumova et al, 2020 ) design. Moreover, statistical comparisons between the two designs were often not performed ( Enax-Krumova et al, 2020 ; Nahman-Averbuch et al, 2013 ; Ram et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%